Revision of the Pachycondyla wasmannii-group (Hymenoptera: Formicidae) - Rakotonirina, Jean Claude; Fisher, Brian L. (Zootaxa, 2013)
Defining species limits and describing species of ants are important to identify taxa and habitats with elevated diversity in areas of high conservation priority such as the Malagasy region. The Pachycondyla wasmannii-group is revised in the Malagasy region where eight species are recognized, four of which are new: P. masoala sp. n., P. planicornis sp. n., P. tavaratra sp. n., and P. vazimba sp. n. Four species have been previously described: P. cambouei Forel, P. comorensis (André), P. perroti Forel, and P. wasmannii Forel. Pachycondyla perroti admista Forel is newly synonymized under P. perroti. Pachycondyla cambouei is widespread in eastern Madagascar, morphologically variable, and divided into seven morphotypes. An identification key to species and distribution maps are provided for the genus in the Malagasy region. All species are known only from Madagascar except P. wasmannii, which occurs also on Anjouan of the Comoros Islands.